Komunikasi Lintas Agama Di Kampung Toleransi: Studi Deskriptif Gang Luna Kampung Toleransi Kelurahan Jamika Kecamatan Bojongloa Kaler Kota Bandung - Gunawan, Aji (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2017)
This study aims to examine communication activities as a process of social interaction in Kampung Toleransi, Bandung City, a multi-ethnic and plural city. The focus of this research is on efforts to build interfaith social interactions and their impact on interfaith tolerance. The findings indicate a synergy of togetherness contributing to the creation of interfaith tolerance and societal harmony. The study was conducted in Gg Luna RW 04 Kampung Toleransi, Jamika Village, Bojongloa Kaler District, using a qualitative descriptive approach. The analysis is based on Lasswell's communication theory, with its elements such as communicator, message, media, receiver, and effect, as well as the symbolic interactionism theory to align perceptions among interfaith communities. Keywords : communication; tolerance; religious